2018
DOI: 10.1093/pm/pny151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient–Provider Interactions Regarding the Burden and Treatment of Opioid-Induced Constipation in Adults with Chronic Noncancer Pain

Abstract: In this analysis, when opioid-induced constipation was discussed, health care providers did not inquire about specific symptoms for most patients, opioids were not cited as a cause of constipation in approximately one-quarter of patients with opioid-induced constipation, and no clear treatment plan or guidance was recommended for one-third of patients. Results of this analysis suggest that more education may be needed to improve patient-provider communication about opioid-induced constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similar to the results seen herein, in a previous survey more than half of patients were not adequately counseled about constipation, and as a consequence altered their opioid regimen to compensate for OIC [ 20 ]. Along these lines, a retrospective analysis of 216 patient–provider discussions in the United States also found that HCP counseling and management of OIC was inadequate, and that in around 30% of cases no specific treatments or guidance was given [ 30 ]. Our findings mirror those results, since a prescription for OIC was given in only around one-third of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results seen herein, in a previous survey more than half of patients were not adequately counseled about constipation, and as a consequence altered their opioid regimen to compensate for OIC [ 20 ]. Along these lines, a retrospective analysis of 216 patient–provider discussions in the United States also found that HCP counseling and management of OIC was inadequate, and that in around 30% of cases no specific treatments or guidance was given [ 30 ]. Our findings mirror those results, since a prescription for OIC was given in only around one-third of cases.…”
Section: Discussionmentioning
confidence: 99%
“…20 This strategy was intended to increase the sensitivity for detecting patients with constipation, considering some patients using laxatives may not have been diagnosed as such in the EMR, as a previous study found that many patients do not discuss constipation with their medical provider. 46 Another related benefit is that this strategy may identify patients taking laxatives for constipation related to a “constipation only” form of IBS, which was not included in the constipation outcome.…”
Section: Methodsmentioning
confidence: 99%
“…A recent large-scale analysis of a database of more than 100,000 patient-provider conversations revealed that patient education was largely insufficient in a majority of cases with only 1 in 10 patients with OIC discussing the problem with the healthcare provider. Furthermore, it was found that specific action was recommended only in a disconcerting one third of these cases [22].…”
Section: Main Bodymentioning
confidence: 99%